The Application of English Songs in Teaching Conditional Sentences through Google Classroom - Fitriyatul Ulyah; Khoirul Anwar; Nirwanto Maruf (Budapest International Research and Critics University, 2021)
This current research investigated the effectiveness of application English songs in teaching conditional sentences through google classroom as a variety of teaching among students to gain interest and motivation. An experimental approach with a pre-test and post-test was exploited. The data was collected through multiple choices test of conditional sentences. A small group of students as the experimental group (N= 32), and another small group as the control group (N=32). A questionnaire was also administered to measure students’ perceptions toward Google classroom in learning conditional sentences through English songs. The finding indicated that there was differences in mean score of experiment and control group although in medium level. Meanwhile, students’ perception towards implementation of GC bring positive effect to the students’ motivation in learning conditional sentences through English songs. Overall, the research presents discerning implication to the body of research on teaching conditional sentences.